Harmful and beneficial effects of UV radiation and photoprotection - knowledge among medical students and non-dermatology physicians. - Frącz, Gabriela; Dobko, Katarzyna; Glac, Agata; Kuliga, Klaudia; Musz, Kinga; Sejnowska, Natalia; Socha, Agnieszka; Surowiec, Agata; Śnieżek, Kinga; Zając, Anna (Journal of Education, Health and Sport, 2023)
Introduction: Exposure to UV radiation promotes skin damage, photoaging and photocarcinogenesis. Photoprotection reduce the negative effects of ultraviolet rays. However, ultraviolet light has some beneficial effects like the production of vitamin D. It is also used in the treatment of some skin diseases. Aim of the study: The aim of the study was to assess the knowledge of medical students and non-dermatology physicians on the harmful and beneficial effects of UV radiation and photoprotection. Materials and methods: The research material was collected using an anonymous online survey. The obtained results were analyzed and verified on the basis of scientific literature and statistically processed using Microsoft Office Excel. Results: 95.3% of respondents believe that knowledge about the effects of radiation is important in medical practice and 98.8% can name at least one skin cancer whose risk factor is UV radiation. All of respondents believe that UVR affects the aging of the skin. 77.8% of respondents know the meaning of the term "SPF". 81.9% are aware that UVB radiation affects the synthesis of vitamin D and 72.0% can indicate at least two dermatoses in which phototherapy is used. Conclusion: Medical students and doctors have a lot of knowledge about the effects of UV radiation and it is important in their medical practice. Increasing awareness about radiation, forms of sun protection and a more thorough physical examination can have a significant impact on patient health. Great vigilance and noticing a suspicious change accelerates the start of treatment and determines the success of the therapy.